Does an immobilization mask have added value during planning magnetic resonance imaging for stereotactic radiotherapy of brain tumours?. (January 2020) - Nagtegaal, Steven H.J.; van Lier, Astrid L.H.M.W.; den Boer, Anne A.; Kramer, Miranda C.A.; Fanetti, Giuseppe; Eppinga, Wietse S.C.; Philippens, Marielle E.P.; Verhoeff, Joost J.C.; Seravalli, Enrica
Highlights: Accurate radiotherapy planning is crucial for brain tumours. Current use of immobilization masks may cause discomfort. The effect of scanning without a mask falls within acceptable bounds of error. There is no benefit in immobilizing the head during MRI for radiotherapy planning. Abstract: Background and purpose: When using an immobilization mask, a magnetic resonance imaging (MRI) head receive coil cannot be used and patients may experience discomfort during the examination. We therefore wish to assess the added value of an immobilization mask during all MRI scans intended for cranial stereotactic radiotherapy (SRT) planning. Materials and methods: An MRI was acquired with and without a thermoplastic immobilization mask in ten patients eligible for SRT. A planning computed tomography (CT) scan was also made, to which the two MRIs were independently registered. Additionally, the MRI without immobilization was registered to the MRI in mask. On each sequence, gross tumour volume (GTV), the right eye, brain stem and chiasm were delineated. The absolute differences in centre-of-gravity coordinates and Dice coefficients of the volumes of the delineated structures between the two MRIs were compared. Results: Differences in GTV volume between the two MRIs were low, with median Dice coefficients between 0.88 and 0.91. Similarly, the median absolute differences in centre-of-gravity coordinates between the GTVs, organs at risk and landmarks delineated on the two MRIs were within 0.5 mm. The 95% confidence intervals of the median absolute differences in the three GTV coordinates was within 1 mm, which corresponds to the target volume safety margin used to account for possible errors during the SRT treatment chain. Conclusions: The effect of scanning a patient without the immobilization mask falls within acceptable bounds of error for the geometrical accuracy of the SRT treatment chain. Consequently, placing the head in treatment position during all MRI scans for patients undergoing radiotherapy of brain metastasis is deemed unnecessary.